Urinary Meatal Swabbing Detects More Men Infected With Mycoplasma genitalium and Four Other Sexually Transmitted Infections Than First Catch Urine. Issue 8 (August 2017) - Chernesky, Max; Jang, Dan; Smieja, Marek; Arias, Manuel; Martin, Irene; Weinbaum, Barbara; Getman, Damon
Abstract : Abstract: Urinary meatal swabs compared with urine showed higher infection rates for Mycoplasma genitalium (15.3% vs 12.6%, P = 0.035), Chlamydia trachomatis (11.3% vs 9.3%, P = 0.039), Neisseria gonorrhoeae (1.4% vs 1.1%, P = 1.00), Trichomonas vaginalis (8.0% vs 1.7%, P < 0.001), and high-risk human papillomavirus (5.9% vs 3.4%, P = 0.078) respectively. Abstract : Urinary meatal swabs compared with first catch urine detected more men infected with Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and high-risk human papilloma virus.